Communication of monetary policy in unconventional times - Günter Coenen; Michael Ehrmann; Gaetano Gaballo; Peter Hoffmann; Anton Nakov; Stefano Nardelli; Eric Persson; Georg Strasser (European Central Bank (ECB), 2017)
Monetary policy communication is particularly important during unconventional times, because high uncertainty about the economy, the introduction of new policy tools and possible limits to the central bank's toolkit could hamper the predictability of policy actions. We study how monetary policy communication should and has worked under such circumstances. Our main results relate to announcements of asset purchase programmes and the use of forward guidance. We show that announcements of asset purchase programmes have lowered market uncertainty, particularly when accompanied by a contextual release of implementation details such as the envisaged size of the programme. We also show that forward guidance reduces uncertainty more effectively when it is state-contingent or when it provides guidance about a long horizon than when it is open-ended or covers only a short horizon, and that the credibility of forward guidance is strengthened if the central bank also has embarked on an asset purchase programme.
Keywords: E43; E52; E58; 330; central bank communication; unconventional monetary policy; asset purchase programme; forward guidance